Answer:
the begging explanation
Step-by-step explanation:
hope this helped
Answer:
x=2
Step-by-step explanation:
![x^{2} -14=-10\\](https://tex.z-dn.net/?f=x%5E%7B2%7D%20-14%3D-10%5C%5C)
Add 14 to both sides
![x^{2}=4](https://tex.z-dn.net/?f=x%5E%7B2%7D%3D4)
Square root it
x=2
Answer:
![-3 ± 2\sqrt{3} = x](https://tex.z-dn.net/?f=-3%20%C2%B1%202%5Csqrt%7B3%7D%20%3D%20x)
Step-by-step explanation:
x² + 6x + 9 = 12 → x² + 6x - 3
Since this Quadratic Expression is unfactorable, apply the <em>Quadratic</em><em> </em><em>Formula</em>:
![x = -b ± \frac{\sqrt{{b}^{2} - 4ac}}{2a}](https://tex.z-dn.net/?f=x%20%3D%20-b%20%C2%B1%20%5Cfrac%7B%5Csqrt%7B%7Bb%7D%5E%7B2%7D%20-%204ac%7D%7D%7B2a%7D)
![-6 ± \frac{\sqrt{{6}^{2} - 4(1)(-3)}}{2(1)} = -6 ± \frac{\sqrt{36 + 12}}{2} = -6 ± \frac{\sqrt{48}}{2} \\ \\ -3 ± 2\sqrt{3}](https://tex.z-dn.net/?f=%20-6%20%C2%B1%20%5Cfrac%7B%5Csqrt%7B%7B6%7D%5E%7B2%7D%20-%204%281%29%28-3%29%7D%7D%7B2%281%29%7D%20%3D%20%20%20-6%20%C2%B1%20%5Cfrac%7B%5Csqrt%7B36%20%2B%2012%7D%7D%7B2%7D%20%3D%20-6%20%C2%B1%20%5Cfrac%7B%5Csqrt%7B48%7D%7D%7B2%7D%20%5C%5C%20%5C%5C%20-3%20%C2%B1%202%5Csqrt%7B3%7D)
√48 = √[3 × 16] = 4√3
½[4√3] = 2√3
Then attach half of -6 to it as well [-3]:
-3 ± 2√3
I am joyous to assist you anytime.
The simplest form of
6
2
is
3
1
.
Steps to simplifying fractions
Find the GCD (or HCF) of numerator and denominator
GCD of 6 and 2 is 2
Divide both the numerator and denominator by the GCD
6 ÷ 2
2 ÷ 2
Reduced fraction:
3
1
Therefore, 6/2 simplified to lowest terms is 3/1.